The Great Lockdown : International Risk Sharing Through Trade and Policy Coordination - Engler, Philipp; Pouokam, Nathalie; Rodriguez Guzman, Diego; Yakadina, Irina (Washington, D.C. : International Monetary Fund, 2020)
Voluntary and government-mandated lockdowns in response to COVID-19 have caused causing drastic reductions in economic activity around the world. We present a parsimonious two-country-SIR model with some degree of substitutability between home and foreign goods, and show that trading partners' asynchronous entries into the global pandemic induce mutual welfare gains from trade. Those gains are realized through exchange rate adjustments that cause a temporary reallocation of production towards the economy with the lowest infection rate at any point in time. We show that international cooperation over containment policies that aim at optimizing global welfare further enhances the ability of countries to exploit trade opportunities to contain the spread of the pandemic. We characterize the Nash game of strategic choices of containment policies as a prisoners' dilemma.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet